Exploring Housing Subsidies to Households in Russia - Hamilton, Ellen; Banerjee, Sudeshna Ghosh; Lomaia, Maka (2012)
Since the early 1990s, the Russian government has undertaken a series of reforms intended to change the system from one where housing and communal services (HCSs) were nearly free to one where residents paid the costs of their housing while protecting vulnerable families. Although households payments have increased, subsidies for HCSs remain substantial (about 4 per cent of GDP) and are exceeded only by public spending for pensions. This paper uses newly available data to analyse recipients of the two major housing subsidy programs. We find that neither l'goti (which are not targeted) nor allowances (which are supposed to be targeted) have provided much protection for poorer households from tariff increases.